Effects of Tillage Methods and Physico-chemical Properties of Soil on Agro-morphological Properties and Yield of Cassava (Manihot esculenta Crantz) in Abongoua, Côte d'Ivoire - René, N’ganzoua Kouamé; Ambroise, N’dakou Koua; Guillaume, Kouame Amany; Zoumana, Konate; Sidiky, Bakayoko (Research Advances and Challenges in Agricultural Sciences Vol. 8, 2024)
The present study determines the effects of tillage methods and physico-chemical properties of soil on agro-morphological properties and yield of Cassava (Manihot esculenta Crantz) in Abongoua, Côte d'Ivoire. Various cultivation techniques have been initiated, including plowing, which aims to create a favorable environment in the soil for the development of cultivated plants. It is through these cultivation techniques improve the structure of the soil, and its physical state and consequently increase its permeability and porosity, creating conditions more suitable for the development of tuberous roots. The experiment was conducted in the field for 13 months (June 2019 to July 2020) in Abongoua in the department of Bongouanou (East-central Côte d'Ivoire). After cleaning a 900 m2 fallow surface and cleaning all plant debris, soil samples were taken with an auger in the 40 cm surface in each corner and in the center of the experimental plot to form the composite sample for laboratory analysis. The cuttings were directly sown at a rate of 12 cuttings per treatment. The data for the various parameters obtained were subjected to an analysis of variance (ANOVA) using SAS software version 9.4, and the means were separated using the Newman and Keuls test at the 5% probability level. The findings revealed an acidic soil with a sandy texture and an abundance of nutrients, particularly major elements, trace elements, and the clay-humus complex. In decreasing order of importance, treatments T3 (ridged soil), T2 (mounded soil), and T1 (tilled soil) produced good growth and development of agro-morphological parameters as well as yield (T0). The study clearly demonstrated that the kind of tillage, particularly the ridged tillage technique, enhances cassava agromorphological parameters, productivity, and yield. What we recommend to farmers in the area for a good cassava harvest in Abongoua, East-Central Côte d'Ivoire.